Localized and Short‐Term Effects of Lockdowns on Urban Rental Markets: Evidence From Shanghai - Yanpeng Jiang; Xiaochi Shen (International Studies of Economics)
ABSTRACT This paper investigates the localized and short‐term effects of COVID‐19‐induced lockdowns on Shanghai's rental market in the second half of 2022. Using Difference‐in‐Differences methodologies, we find that rental prices declined by 1.5% following the lockdowns on average, with areas characterized by a high density of companies falling by 2.0% and no significant change in suburban areas. Event‐study analysis further reveals that this decline peaked at 3.0% 2 months post‐lockdown. This decline was temporary with rental prices returning to pre‐lockdown levels within 12 months. Robustness checks and comparisons with housing sale prices confirm the absence of significant spillover effects or structural shifts. These findings underscore the localized and temporary nature of lockdown‐induced disruptions in the rental market and may be valuable to housing policymakers considering responses to short‐term crises.